2001
DOI: 10.1093/oxfordjournals.rpd.a006535
|View full text |Cite
|
Sign up to set email alerts
|

Effective Doses and Organ Doses in the MIRD-5 Phantom Exposed to Monoenergetic 0.1 MeV to 200 MeV Electrons in the LAT Direction

Abstract: Organ doses and effective doses were calculated using the EGS-4 Monte Carlo simulation code and a MIRD-5 mathematical human phantom placed in a vacuum. For broad right and left lateral beams of monoenergetic (0.1-200 MeV) electrons, conversion coefficients from the incident fluence to organ dose, to effective dose, and to effective dose equivalent were obtained. There were no clear differences between the conversion coefficients in the case of left-lateral (LLAT) and right-lateral (RLAT) irradiation. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…PtdCho is not only a structural component; it can also be converted to phosphatidic acid (PA) and free choline (Cho) by phospholipase D (PLD). Importantly, recent studies using plant cell cultures have suggested that PA may also be a signaling molecule that acts as a second messenger in diverse processes during plant development [19,25,26,30]. Therefore, PEAMT is not only the key enzyme in PtdCho biosynthesis, but could also be important for the production of Cho and PA in plants.…”
Section: Introductionmentioning
confidence: 99%
“…PtdCho is not only a structural component; it can also be converted to phosphatidic acid (PA) and free choline (Cho) by phospholipase D (PLD). Importantly, recent studies using plant cell cultures have suggested that PA may also be a signaling molecule that acts as a second messenger in diverse processes during plant development [19,25,26,30]. Therefore, PEAMT is not only the key enzyme in PtdCho biosynthesis, but could also be important for the production of Cho and PA in plants.…”
Section: Introductionmentioning
confidence: 99%